Effectiveness and compliance of an oscillating-rotating toothbrush in patients with dental implants: a randomized clinical trial - Giuseppe Allocca; Diana Pudylyk; Fabrizio Signorino; Giovanni Battista Grossi; Carlo Maiorana (SpringerOpen, 2018)
Abstract Background The aim of this randomized clinical trial was to assess the efficacy of an oscillating-rotating toothbrush in reducing plaque and inflammation around dental implants. Methods Eighty patients presenting dental implants were enrolled in this study and assigned randomly to two different groups: 40 patients in the test group and 40 in the control one. Each patient in the test group received an oscillating-rotating toothbrush while in the control group patients kept using the manual toothbrush. Furthermore, the test group received a special toothbrush head designed for dental implants and another one for natural teeth. Domiciliary oral hygiene instructions were given to both groups. Periodontal parameters like plaque index (PI), bleeding on probing (BoP), and probing pocket depth (PPD) were recorded at the baseline and after 1 and 3 months. Results At the end of the study, the difference of plaque and bleeding indices with the baseline was statistically significant for both test and control groups (P < 0.0001). Implant sites showed higher values of both BoP and PI when compared to the natural teeth. In the second part of the study, comparing the 1-3-month period, the oscillating-rotating toothbrush was effective in reducing new plaque formation (P < 0.0001) and bleeding (P < 0.0001) both at the implant sites and the dental sites comparing to manual ones (P > 0.05). No significant differences were appreciated concerning the PPD. Conclusions The oscillating-rotating toothbrush can be successfully used for the plaque and bleeding control of the peri-implant tissues.